Study on the Suitability of Green Mussel (Perna viridis) Culture in North Sea Waters of Java, Ketapang Village, Tangerang District, Banten Province - rinrin haryanti; Achmad Fahrudin; Handoko Adi Susanto (Journal of Aquaculture and Fish Health, 2019)
Green mussel is one of the fisheries resources have to be developed to prospective higheconomically valuable commodities .This is proportional to the nutrition beef , eggs and chicken .This indicates that green shell are mostly potential can be developed through the cultivation .The study is done at july until august sea north of java in 2019 , the village Ketapang , Mauk district , Tangerang , Banten .The data under the four station representing village ketapang waters .The methodology used by approaching purposive sampling method uses the data analysis by the ratings point .The village ketapang skoring waters that is both life and research sites support green shell that could be used as the green mussel cultivation .